O espaço que ousa dizer seu nome: territórios GLTBS de Goiânia - Sousa, Alemar Moreira de (2005)
The boarding of cultural geography if develops as "a way" to consider and to understand these "new" objects of research, excited for the changes in the world contemporary. The agreement of the construction of the notion of territory to the long one of geographic science, as well as the elaborated territorial dynamics from the geography of the sort they foundation the formation of identity territories GLTBS (Gays, Lesbians, Transgenders, Bissexuals, Sympathetical). Ahead of the complexity of the metropolises contemporaries we evidence, in Goiânia, a repertoire of territories GLTBS and detach to the relations between these, in special the Domingueira Millenium. We understand that the right to the citizenship it involves the territorial question, therefore many times are denied to the GLTB the right to the city. But, she is necessary to go beyond the limits of territories GLTBS not constructing "small oases" surrounded by an immense desert of not to undertand and not tolerance.